Efficient Path Planning Based On Hybrid Routing Protocols over A Vanet - Prabha, S. Santhana (IJRDO -Journal of Computer Science Engineering, 2017)
Vehicular Ad-hoc Network (VANET) is anemerging communication Infrastructure whichfacilitates the connectivity among vehicles throughvehicle-to- vehicle (v2v) and vehicle-to-roadside (v2R)communications and is characterized by high dynamictopology of nodes in the network. Due to this highmobility of vehicles it is quite challenging to performpacket delivery from source to destination in case of anydestruction or congestion in the network. In order toovercome this problem a novel path planning techniquemust be implemented reducing packet loss and end toend delay which includes communication amongvehicles, road side units(RSUs) and vehicle trafficservers. Hence we propose a routing protocol with GPSand map aware capabilities that includes four metricssuch as distance to destination, vehicle’s density,vehicle’s trajectory and available bandwidth in order tomake forwarding decisions. This protocol is beingjustified and it is shown that it reduces packet loss andend to end delay in the network thus increasing theefficiency of routing.